Healthcare Providers' Responses to Narrative Communication About Racial Healthcare Disparities. Issue 2 (28th January 2019) - Burgess, Diana J.; Bokhour, Barbara G.; Cunningham, Brooke A.; Do, Tam; Gordon, Howard S.; Jones, Dina M.; Pope, Charlene; Saha, Somnath; Gollust, Sarah E.
ABSTRACT: We used qualitative methods (semi-structured interviews with healthcare providers) to explore: 1) the role of narratives as a vehicle for raising awareness and engaging providers about the issue of healthcare disparities and 2) the extent to which different ways of framing issues of race within narratives might lead to message acceptance for providers' whose preexisting beliefs about causal attributions might predispose them to resist communication about racial healthcare disparities. Individual interviews were conducted with 53 providers who had completed a prior survey assessing beliefs about disparities. Participants were stratified by the degree to which they believed providers contributed to healthcare inequality: low provider attribution (LPA) versus high provider attribution (HPA). Each participant read and discussed two differently framed narratives about race in healthcare. All participants accepted the "Provider Success" narratives, in which interpersonal barriers involving a patient of color were successfully resolved by the provider narrator, through patient-centered communication. By contrast, "Persistent Racism" narratives, in which problems faced by the patient of color were more explicitly linked to racism and remained unresolved, were very polarizing, eliciting acceptance from HPA participants and resistance from LPA participants. This study provides a foundation for and raises questions about how to develop effective narrative communication strategies to engage providers in efforts to reduce healthcare disparities.